Effect of ohmic heating on colour and texture of chicken frankfurter - J Lim-im; C Kulketwong; N Suwanpayak; D Thungsotanon (My University, 2019)
Abstract Ohmic method is a heating technique using the electrical current directly through the food. In this study, the commercial chicken frankfurters were heated by an alternating current in a voltage range of 45-55 V and compared the qualities in term of colour, texture, moisture content and water activity with the non-heating. The voltage gradient was conversely correlated with the heating duration. The high voltage gradient could raise the target temperature in a short time but it provided the less shear force of specimen tenderness. On the other hand, every voltage insignificantly influenced the sausage moisture content. The large amount of the water activity was significant decreased at the voltage gradient of 50 V and the hardness and the shearing level of the sample of this intensity were similar to the non-heating sausage. The specimens with ohmic heating seemed homogeneous colour with naked eye whereas the measured values were slightly different.
Keywords: Texture (cosmology); Shearing (physics); Shear force; Temperature Gradient; Meat and Animal Product Quality